Особенности спонтанного расселения древесных растений, интодуцированных на юго-востоке Украины - Осавлюк, С.Н. (Промышленная ботаника, 2004)
21 species of berry-producing trees and shrubs introduced in the Donetsk Botanical Gardens have been investigated and the peculiarities of their spontaneous distribution both over the collection plot and out of it have been revealed. The mechanisms of the distribution, ability to self-sowing and formation of the morphological structures for vegetative reproduction have been determined. A conclusion was made concerning the species’ possible naturalization and prospective invasion into the native phytocenoses of the south-east of Ukraine.